Fracture resistance of roots with simulated internal resorption defects and obturated using different hybrid techniques - Özgür İlke Ulusoy; Yelda Nayır Paltun (Elsevier, 2017)
Background/purpose: Teeth with internal resorption are susceptible to fracture because of the remaining thin dentinal walls. The aim of this study was to investigate the fracture resistance of roots with simulated internal resorption cavities and obturated with different hybrid techniques. Materials and methods: Seventy single root canals were instrumented. On the coronal half of the roots, standardized internal cavities with a length of 8 mm were created. The apical 6 mm of the 60 root canals were filled with AH Plus sealer and gutta-percha cones. Then, 80 roots were divided into four experimental groups and two control groups according to the internal cavity obturation: Group 1, AHPlus sealer + high-temperature thermoplasticized injectable gutta-percha; Group 2, DiaRoot Bioaggregate; Group 3, Biodentine; Group 4, MTA Fillapex; Group 5, instrumented, but not obturated roots; Group 6, intact roots. A compressive vertical loading at a speed of 1 mm/min was applied to the roots. The forces when the fracture occurred were statistically analyzed with one-way analysis of variance and post hoc Tukey test. Results: Biodentine group showed statistically higher resistance to fracture than the other experimental groups (P < 0.05). Conclusion: Filling the internal resorption cavities with thin dentinal walls using Biodentine may provide strength to the tooth structure more than the other calcium silicate-based materials.